Teknologi Pemanfaatan Serat Daun Nanas Sebagai Alternatif Bahan Baku Tekstil - Pratikno Hidayat (Faculty of Industrial Technology Universitas Islam Indonesia, 2008)
At present the pineapple plant is widely cultivated in some regions of Indonesia. Nevertheless the plantation of pineapple plants are commonly utilised only for fruit. This paper aim to represent the another benefit of pineaple plants which can be utilised their abundant pineaple leafs to be used for the textile material, known as pineapple leaf fibres. This subject consist of a review of investigation carried out on the method of making pineapple leaf fibres such as decortication and degumming pocesses, some properties of pineapple leaf fibres, and their appropriateness for manufacturing of textiles as yarns or fabrics. An relation of the possible use of pineapple leaf fibres as related products is also given. Keywords: pineapple leaf fibres, decortication, and degumming process.